2018
DOI: 10.1183/13993003.01562-2018
|View full text |Cite
|
Sign up to set email alerts
|

Role of anlotinib-induced CCL2 decrease in anti-angiogenesis and response prediction for nonsmall cell lung cancer therapy

Abstract: The underlying molecular mechanisms and predictive biomarkers of anlotinib benefitting NSCLC patients are still unclear. In this study, anlotinib-induced CCL2 decrease contributes to a novel insight for its anti-angiogenesis mechanism and responsive prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…There were some studies con rmed that the expression level of VEGF in tumor is negatively related to poor prognosis (41). As a new type of small molecule and multitargeting TKI, anlotinib mainly acts through the VEGF pathway to exert an anti-tumor role (39,42). In 2020, oncologists from the European Cancer Research Institute suggested that anlotinib has intracranial activity and could control intracranial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were some studies con rmed that the expression level of VEGF in tumor is negatively related to poor prognosis (41). As a new type of small molecule and multitargeting TKI, anlotinib mainly acts through the VEGF pathway to exert an anti-tumor role (39,42). In 2020, oncologists from the European Cancer Research Institute suggested that anlotinib has intracranial activity and could control intracranial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…CRT can increase the permeability of the BBB, and increase drug concentration in the central nervous system (33). Anlotinib normalizes the blood vessels in a metastatic tumor, improves the internal microenvironment of the tumor, restores the normal permeability of the blood vessels, and plays a synergistic role with CRT to enhance radiosensitivity and reduce brain edema (8,(41)(42)(43)(44). However, further work is required to determine whether the combination of anlotinib and CRT is better than CRT alone for patients with BM from lung cancer who failed to respond to multi-line chemotherapy or were resistant to treatment with EGFR/ALK-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Anlotinib-induced inhibition of angiogenesis and proliferative signaling contributed to the phenomenon [6,7]. Molecular mechanism study suggested the targets of anlotinib include CCL2 signaling pathway, receptor tyrosine kinases vascular endothelial growth (VEGFR) signaling pathway, endothelial growth factor receptor (EGFR) signaling pathway, broblast growth factor receptor (FGFR) signaling pathway, and so on [8,9]. The characteristics of this multi-target tyrosine kinase inhibitor (TKI) make a great di cult for clinical biomarker screening.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that anlotinib could induce protective autophagy, related to anti-angiogenic property of multikinase inhibitor anlotinib (6). Lu et al (7) believe that anlotinib-induced serum CCL2 level decreases were associated with the benefits of PFS and OS in refractory advanced NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%